(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
In this article, we will try to convey to our young generation the perseverance of the people of Uzbekistan and the fact that they sacrificed their lives for the country. In 1939, people worked tirelessly to build the Fergana canal. In 1940, dark days began to befall our people, and we were informed about the beginning of the war. The war between Germany and the USSR did not fail to show its effect on our people.